A Meta‐Analysis of Maize and Wheat Yields in Low‐Input vs. Conventional and Organic Systems. (1st May 2016) - Hossard, Laure; Archer, David W.; Bertrand, Michel; Colnenne‐David, Caroline; Debaeke, Philippe; Ernfors, Maria; Jeuffroy, Marie‐Helene; Munier‐Jolain, Nicolas; Nilsson, Chris; Sanford, Gregg R.; Snapp, Sieg S.; Jensen, Erik S.; et al.
Abstract : Organic and low‐input systems are proposed as ways to reduce the environmental impacts of agriculture. Previous studies have shown that yields of organic systems can be ∼19 to 25% lower than conventional systems. An intermediary, low‐input system could be less damaging for the environment than conventional systems, while reducing yield losses in comparison with organic systems. In this study, we performed a meta‐analysis to compare low‐input systems to conventional and organic systems. Our analysis is based on data of cropping system experiments conducted in Europe and North America, and focuses on two important crops, maize ( Zea mays L.) and soft winter wheat ( Triticum aestivum L.). Pesticide use was greatly reduced for low‐input systems as compared with conventional for the two crops (50% for maize, 70% for wheat on average). Mean mineral N use was also reduced by 36% for maize and 28% for wheat in low‐input relative to conventional. Maize yields in low‐input systems were not different from those in conventional systems, and were higher than yields in organic systems (yield ratio of low‐input vs. organic = 1.24). Wheat yields in low‐input systems were lower than yields in conventional systems (yield ratio of low‐input vs. conventional = 0.88), but were substantially higher than yields in organic systems (yield ratio of low input vs. organic = 1.43). This is one of the first meta‐analyses to assess performance in terms of pesticide use intensity, and yields, with clear evidence emerging that low‐input systems can markedly reduce pesticide application, without strongly reducing crop yields, relative to conventional systems. Core Ideas Maize yields are equivalent for tested low‐input and conventional systems. Maize yields are on average 24% higher for tested low‐input relative to organic. Wheat yield average is 12% lower in tested low‐input than in conventional systems. Wheat yields are on average 43% higher for tested low‐input relative to organic. Mean pesticide use is more than halved in low‐input compared to conventional systems.